PENGARUH CAPITAL ADEQUACY RATIO DAN BOPO TERHADAP NON PERFORMING LOAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wellanda, Elsa; Sianturi, Romauli; Pangaribuan, Fransisco; Amelia, Lois; Dini, Siti (Aksara Public, 2019)
The study aims to investigate the influence of Capital Adequacy Ratio, Operational Costs Operational Income to Performing Loan in banking company listed on the Indonesia Stock Exchange in 2013-2017. This study uses quantitative data that have been published in the Indonesia Stock Exchange (BEI). The population used in the study is the banking company listed in Indonesia stock exchange 2013-2017 totaling 43 companies. The sample used in the study as many as 31 companies using purposive sampling method. Testing the hypothesis in the study using multiple linear regression analysis, t test, f test and coefficient of determination. The results showed that partially Capital Adequacy Ratio no influence positive and no significant to Non Performing Loan, while Opertional Costs and Operational Income that partially influence positive and significant to Non Performing Loan. Simultaneously Capital Adequacy Ratio and Operational Costs Operational Income influence and significant on the on Performing Loan. Where the error rate used is 5% or 0.05 at significant level of 95%.